Frequency of Arthropods Daily Visits on Centella asiatica L. and Synedrlla nodiflora (L) Gaertn in the Wonosari Singosari Tea Plantation Area in Malang Regency - Dora Dayu Rahma Turista; Fatchur Rohman; Bagyo Yanuwiadi (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2020)
The purpose of this research is to find the temporal distribution pattern of the visiting of Arthropods on these wild plants. This descriptive and explorative research was carried out in the Wonosari tea plantation, Singosari, Malang in March 2011. The visual control method for these purposes was adopted from the modification of the visual control method developed by Frei and Manhart (1992). Observations were done with 10 repeats, consisting of 10 tempos with 15 minutes duration. Data relating to the temporal distribution of Arthropods on these wild plants were presented as diagrams and interpreted descriptively. The result of this research can be described as follows: There was a difference between the temporal distribution of Arthropod visiting the wild plants Centella asiatica L. and Synedrella nodiflora (L) Gaertn. For the Centella asiatica L the highest visitor number was at 10.00 am while for the wild plant Synedrella nodiflora (L) Gaertn it was at 11.20 am.